0195 Carbon nanotube exposure assessment for a study on early biological effects; the CANTES study. (23rd June 2014) - Kuijpers, Eelco; Vermeulen, Roel; Tromp, Peter; Fransman, Wouter; Brouwer, Derk; Godderis, Lode; Vlaanderen, Jelle; Bekker, Cindy; Pronk, Anjoeka
Abstract : Objectives: To assess personal exposure to carbon nanotubes for a study of early effect biomarkers among workers exposed to carbon nanotubes (CNTs). Method: Three major job categories were identified in the exposed factory: production, R&D and office. For qualitative assessment personal 8-hr-TWA inhalable dust samples (n = 5) were collected in all job categories and analysed by SEM-EDX. For quantitative assessment 8-hr TWA samples (n = 30) were collected from the production and R&D workers and analysed for elemental carbon, corrected for soot using SEM/EDX. Job activities were recorded during all measurements. Results: The qualitative analyses demonstrated the presence of CNTs in the personal breathing zone of production, R&D and office workers. CNT agglomerates with particle sizes between 500 nm and 100 μm were identified for production and R&D workers and between 500 nm and 5 μm for office workers. No single CNTs were identified. The quantitative analyses demonstrated geometric mean (GM) inhalable CNT levels of 42.6 μg/m 3 (min-max: 1.4–1186.5) and 4.6 μg/m 3 (min-max: 0.2–59.5) for the production and R&D workers, respectively. Conclusions: We identified exposure to clusters of CNT in production, R&D and office workers of the CNT production facility. As expected GM exposure was higher for production than for R&D workers, however considerable variability was observed. Additional quantitative measurements in office and production workers are ongoing. For the full set, analyses of within- and between-worker variability and activity as a determinant will be performed. This information will be used to assess personal exposure in a cross-sectional study of early health effects in the CANTES study.